CRESustain - Silveira, Clara (2022)
Silveira, C., Santos, V., Reis, L., & Mamede, H. (2022). CRESustain: Approach to Include Sustainability and Creativity in Requirements Engineering. Journal of Engineering Research and Sciences, 1(8), 27-34. https://doi.org/10.55708/js0108004, https://doi.org/10.55708/js0108